The Palestine Nakba : decolonising history, narrating the subaltern, reclaiming memory - Masalha, Nur, 1957- (Zed Books, 2012)
This book explores new ways of remembering and commemorating the Nakba - the most traumatic catastrophe that ever befell Palestinians. Masalha argues that to write more truthfully about the Nakba is not just to practise a professional historiography but an ethical imperative. The struggles of ordinary refugees to recover and publicly assert the truth about the Nakba is a vital way of protecting their rights and keeping the hope for peace with justice alive.